A Contextual Approach E-Learning Materials to Improve Reading Skills of Third-Grade Elementary School Students in Indonesian Language Learning - Cica Marsela Br Sitepu; I Gede Astawan; Gusti Ayu Putu Sukma Trisna (Universitas Pendidikan Ganesha, 2025)
The low reading ability among elementary school students remains a fundamental challenge in early literacy learning. Reading activities that tend to be monotonous and lack contextual relevance often hinder students’ comprehension of texts as a whole. This study aims to develop and examine the feasibility and effectiveness of a contextual-based electronic teaching material (e-module) to enhance the reading skills of third-grade elementary students. The research employed a Research and Development (R&D) design using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The study involved 33 third-grade students as research subjects. Data were collected through questionnaires and observations and analyzed using descriptive quantitative and inferential statistical techniques. The findings revealed that the contextual-based e-module is highly valid, practical, and effective in improving students’ reading skills. Conceptually, this e-module fosters a more meaningful and contextual learning experience, enabling students to understand reading materials through real-life connections. These findings imply that digital teaching materials should be continuously innovated to support adaptive, interactive, and student-centered literacy learning in the 21st century.